SUFISTIC CHARACTER EDUCATION ON ENRHIRIDON STUDIOSII OF AZZARNUJI - Ramdhani, Khalid (Wahana Karya Ilmiah Pendidikan, 2021)
Along with world development civilization on science and technology. The realm of education today seems to be a highlight major public in the sight of social, political, economic and cultural. All dimensions of life seems cynical to the world of education in this globalization era. Starting from the intellectual circle filled with the their rhetoric of the theory of scientific concepts to lay people who do not recognize the bench of studies who speaks with scathing criticism in the rules of education which always changing in according with the demands of the times. But in the middle the rapid development of every aspect of life, felt by the teachers and community widely, as if there is something decreased even almost vanished in a seeker of knowledge (student). The condition of the decline of morality of a student in this generation is getting down dramatically compared with those of previous generations. We need to find an effective and efficient solution in this condition, so that moral decadence does not continue to occur. Education is not only in science and skill oriented but also must keeping the best of values life. If the government with the slogans "Mental Revolution" just as a lieutenant and does not found the right solution in the stages of its application. Then the Values of life will gradually disappear little by little. Whereas the true of this concept will provide a synergistic holistic aspect in a seeker of knowledge (lahiriyah and bathiniyyah). So the thought of Az Zarnuji poured in the book Ta’lim Muta’alim ever translated in Latin as Enchiridon Studiossi is still relevant to be studied and applied on Islamic education today. This book containing the Sufism character which is the classical literature that discusses the learning strategies and concepts of education combined harmoniously with the concept of the teachings of Sufism. Although this is not expressed explicitly by the author, but the concept and strategy of education that he put forward very sufistik with language that always refers to the foundation of ethics-religion. Keyword: Azzarnuji, Talim Muta’alim, Character of Education, Seeker of knowledge.